2021
DOI: 10.35860/iarej.906557
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Spatio-temporal rainfall trends and rainfall variability in Botswana between 1958 and 2019

Abstract: Environments with a climatic characteristic of semi-aridity exhibit high rainfall variability, increasing significantly as the climate changes. In this study, rainfall concentration and Spatiotemporal trends in annual and seasonal (November to March) rainfall in Botswana were analyzed. The satellite data is obtained from the Southern African Science Service Centre for Climate Change and Adaptive Land Management and the Climate Toolbox. The Mann-Kendall trend test (MK), autocorrelation function (ACF), relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…160 This understandably has adverse implications for agriculture and the water sector, leading to food insecurity. 161 A recent study on spatio-temporal rainfall variability in Botswana confirmed a decrease in rainfall in Francistown 162 but, as in the case of Gaborone, Francistown has also been affected by disastrous flooding. 163 Botswana does not have climate change-specific local (city-level) laws and policies, as far as could be established.…”
Section: Botswana: Gaborone and Francistownmentioning
confidence: 98%
See 1 more Smart Citation
“…160 This understandably has adverse implications for agriculture and the water sector, leading to food insecurity. 161 A recent study on spatio-temporal rainfall variability in Botswana confirmed a decrease in rainfall in Francistown 162 but, as in the case of Gaborone, Francistown has also been affected by disastrous flooding. 163 Botswana does not have climate change-specific local (city-level) laws and policies, as far as could be established.…”
Section: Botswana: Gaborone and Francistownmentioning
confidence: 98%
“…154 As in the case of the cities in Zimbabwe and Namibia, droughts and water scarcity affect the agricultural sector and food security in the area. 155 Studies in 2014 indicated a decline in the capacity of the Gaborone Reservoir, which supplies water to the city, such that it was impossible at the time to pump out water. 156 Water scarcity has also historically led to water rationing in Gaborone, which left citizens without water for some days.…”
Section: Botswana: Gaborone and Francistownmentioning
confidence: 99%
“…[44] computed R/S analysis for the residual series obtained after filtering periodicities, showed that they have statistical properties close to the ordinary Brownian noise using Base R.A study by [45] used fluxes calculated using Base R to assess net atmospheric Methane (CH4) fluxes and controlling environmental factors in the Okavango Delta. [46]analysed rainfall concentration and spatio-temporal trends in annual and seasonal November to March rainfall in Botswana. The Precipitation Concentration Index (PCI), Mann-Kendall trend test, Theil-Sen's slope estimator (β), Autocorrelation Function (ACF) and relative percentage change (RPC) methods were adopted for data analysis were performed using Base R. [47]research determine trends in the annual maximum average rainfall for Botswana during the years 1901-2012.…”
Section: R Programming Packages In Climatologymentioning
confidence: 99%